2011
DOI: 10.1016/j.yhbeh.2010.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and the origins of paternal effects

Abstract: Though there are multiple routes through which parents can influence their offspring, recent studies of environmentally induced epigenetic variation have highlighted the role of non-genomic pathways. In addition to the experience-dependent modification of DNA methylation that can be achieved via mother-infant interactions, there has been increasing interest in the epigenetic mechanisms through which paternal influences on offspring development can be achieved. Epidemiological and laboratory studies suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
279
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(296 citation statements)
references
References 100 publications
4
279
0
10
Order By: Relevance
“…Interestingly, the effects observed in human epidemiological studies are qualitatively similar to paternal effects observed in species of laboratory rodents that do not engage in postnatal paternal care (4). Although much of the evidence is, at this stage, preliminary, there is emerging support that environmental induction of paternal germline epigenetic changes can have consequences for multiple generations of offspring.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Interestingly, the effects observed in human epidemiological studies are qualitatively similar to paternal effects observed in species of laboratory rodents that do not engage in postnatal paternal care (4). Although much of the evidence is, at this stage, preliminary, there is emerging support that environmental induction of paternal germline epigenetic changes can have consequences for multiple generations of offspring.…”
Section: Discussionmentioning
confidence: 82%
“…In these species, paternal care may induce changes in offspring development via similar mechanisms as postnatal maternal care. However, few mammalian species (3-5%) provide paternal care, and paternal effects can occur in the absence of paternal care (4). The underlying mechanisms of these paternal effects are perplexing in nonmonogamous mammalian species because the biological information transmitted during fertilization is thought to be limited to paternal DNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, paternal exposure to toxicant and nutritional state as well as age, have been found to influence not only offspring but sometimes grand-offspring. 106 …”
Section: Epigeneticsmentioning
confidence: 99%
“…Environmental toxicant exposures include a wide range of factors such as smoking and air pollution. Whereas most research has focused on the biological impact of prenatal and postnatal exposures, new studies are beginning to show possible transgenerational effects through epigenetic changes in the germline connected with smoke and toxicant exposure which provides an argument for the importance of the preconception health states of parents (Curley et al 2011;Laubenthal et al 2012). …”
Section: The Biology Of Social Adversitymentioning
confidence: 99%